The Impact of Foreign Direct Investment on Employment in Malaysia - Yuvaraja, Gurumurty (2011)
This study aims to examine the influence of foreign direct investment (FDI) on employment in Malaysia. This study period was from 2000 to 2009. This study is divided into five chapters which discuss the influence of FDI on employment in Malaysia. Background studies and research objectives stated in the study. This study also reviews the relationship of gross domestic product (GDP) in nominal prices and a few selected sectors in Malaysia on FDI. Based on the model results show that FDI regression has significant effects on all variables that have been used. Data have been used is the time series. Data analysis is performed using Ordinary Least Square method, the Unit Root Test based on Augmented Dickey-Fuller (ADF) approach and finally using Granger Causality test is employed to test the cointergration in this study. It is processed through the E-view 5.0. The implication of policy and suggestion are discussed on increase the number of employment on foreign direct investment in Malaysia.